(untitled) (Impact: Journal of Transformation, 2024)
Many individuals and large communities in the world lack the will and the ability for true peacebuilding. Truly born-again Christians are best endowed and mandated to be effective peacebuilders, starting from their respective local spaces. Although it is true that Jesus himself was born and lived all his earthly life in a very troubled and peaceless space and died a very violent death, it had been prophesied that, among his other real identities and offices, he would come as the Prince of Peace. Although in his radical teaching he said he did not come to bring peace but a sword, he himself was the most peaceful human being and the most effective peacemaker. He also sent his disciples to violent communities as peaceful emissaries. Before his death, resurrection, and ascension to heaven he gave his special divine peace to his disciples (the first church). Sin is the cause and breeding ground for hatred, conflict, and lack of peace. True salvation in Jesus Christ is the only remedy for sin and the source of power for true love, true personal peace, and genuine peacebuilding. When a person is made righteous through our Lord, Jesus Christ, he or she acquires peace with God. A person who is genuinely justified is able to love genuinely, deliberately abhor wickedness, and decisively live peaceably with all people, thus being a pragmatic peacebuilder. My research method for the paper is historical-grammatical exegesis. Through it, I seek to discover the meaning of peace and peacebuilding in various Bible texts as was intended by the authors to be understood and applied by the original hearers Theological application and recommendations for peacebuilding are proposed for the church in the African setting based on specific Bible texts for specific needs.